2013
DOI: 10.2174/18715281113129990057
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Catechins Quench the Fluorescence of Bacteria-Conjugated Alexa Fluor Dyes

et al.

Abstract: Accumulating evidence suggests that Green tea polyphenolic catechins, especially the (-)-epigallocatechin gallate (EGCG), can be cross-linked to many proteins, and confer a wide range of anti-bacterial activities possibly by damaging microbial cytoplasmic lipids and proteins. At the doses that conferred protection against lethal polymicrobial infection (induced by cecal ligation and puncture), EGCG significantly reduced bacterial loads particularly in the liver and lung. To elucidate its bactericidal mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
(60 reference statements)
1
14
0
Order By: Relevance
“…Even when given orally, EGCG still rescued mice from lethal sepsis, significantly increasing animal survival rates from 16% to 44% [141]. Intriguingly, we found that EGCG facilitated bacterial elimination in selective organs (e.g., the liver and lung) in an animal model of sepsis [147]. It is not yet known whether these antibacterial properties are attributable to the possibilities that EGCG directly kill microbes by altering microbial protein conformations and functions, or indirectly by modulating macrophage-associated innate immune responses.…”
Section: Therapeutic Potential Of Hmgb1-inhibiting Agentsmentioning
confidence: 99%
“…Even when given orally, EGCG still rescued mice from lethal sepsis, significantly increasing animal survival rates from 16% to 44% [141]. Intriguingly, we found that EGCG facilitated bacterial elimination in selective organs (e.g., the liver and lung) in an animal model of sepsis [147]. It is not yet known whether these antibacterial properties are attributable to the possibilities that EGCG directly kill microbes by altering microbial protein conformations and functions, or indirectly by modulating macrophage-associated innate immune responses.…”
Section: Therapeutic Potential Of Hmgb1-inhibiting Agentsmentioning
confidence: 99%
“…5). In light of the findings that EGCG dramatically reduced bacterial loads in the liver [35], it is possible that elevation of peritoneal neutrophils may facilitate elimination of invading pathogens in the peritoneal cavity.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, the elevation of peritoneal G-CSF levels was associated with a specific increase in neutrophil counts in the peritoneal fluid. It remains to be determined whether the elevated G-CSF might have facilitated the proliferation of neutrophil, which may contribute to an effective bacterial elimination during a late stage of sepsis [35]. Indeed, G-CSF has been shown to stimulate the proliferation of neutrophils [36;37], and widely used to accelerate recovery from neutropenia (an abnormal neutrophil deficiency) in cancer patients undergoing chemotherapy [38], preventing cancer patients from subsequent infections and sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 (-)-Epigallocatechin-3-gallate (EGCG), the principal polyphenol in extracts of green tea, has been shown to possess various beneficial effects on cancer, [14][15][16] allergy, 17 hypertension, 18 atherosclerosis, 19 diabetes, 20 as well as bacterial and viral infection. 21,22 EGCG has thus been found to suppress tumor growth and angiogenesis by inhibiting MMP2 and -9 expression in tumor cells. 23,24 Topical administration of EGCG was also shown to inhibit corneal neovascularization in rabbits through suppression of the expression of VEGF and cyclooxygenase-2, 25 to attenuate inflammatory responses of the ocular surface in a mouse model of dry eye, 26 and to limit the development of corneal opacity caused by alkali-burn injury to the cornea in mice.…”
mentioning
confidence: 99%